The Impacts of ENSO and IOD on the MSL of The Arabian Gulf and The Arabian Sea by Using Satellite Altimetry Data - Atyaf Mohammed Abdul Mutalib; Sabah M. M. Ameen; Ali B. Mahmood (Marine Science Department Diponegoro University, 2020)
The main objective for the current research is to determine the linear trends of the mean sea level (MSL) resulting from the influence of the Southern Oscillation of El Niño (ENSO) and the Indian Ocean dipole (IOD), which have increased in recent times due to increased global warming using satellite altimetry of MSL data. Statistical time series technique has been used. The standard ordinary univariate and bivariate linear regression method as well as Pearson correlation were used. Linear trends for the positive phase of IOD were detected on mean sea level while no linear trends of ENSO were detected in the Arabian Gulf. On the other side, linear trends of the negative phases of IOD and ENSO were detected on mean sea level in the Arabian Sea over the period 1993-2013. It is most important for climate research to provide accurate predictions of sea level rise in the coming years and plan the activities to lessen the disasters before they happen.